2006
DOI: 10.1038/sj.bjc.6603108
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A and Poly(A) binding protein-interacting protein 2 expression in human head and neck carcinomas: correlation and prognostic significance

Abstract: Vascular endothelial growth factor-A (VEGF-A) has been demonstrated to play an important role in tumour angiogenesis and to influence prognosis in many cancers. However its prognostic value in head and neck squamous cell carcinomas (HNSCCs) remains controversial. Therefore, we investigated the clinical relevance of VEGF-A expression in HNSCCs and analysed whether its expression was associated with PAIP2 protein levels, a VEGF-A mRNA-binding partner that strongly regulates VEGF-A expression in tissue culture. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
2
18
0
4
Order By: Relevance
“…Many studies have shown that VEGF-A, as well as VEGF-C, are upregulated in head and neck cancers, thus stimulating proliferation of vascular and lymphatic endothelial cells, and increasing vessel permeability (Thomas et al, 2005). The enhanced angiogenic activity could sustain growth of the primary tumour, potentiate dissemination and also support the establishment of micrometastases (Onesto et al, 2006). This is consistent with the strong association observed in different studies between VEGF-A expression and distant recurrence.…”
Section: Vascular Endothelial Growth Factor-a (Vegf-a)supporting
confidence: 79%
See 3 more Smart Citations
“…Many studies have shown that VEGF-A, as well as VEGF-C, are upregulated in head and neck cancers, thus stimulating proliferation of vascular and lymphatic endothelial cells, and increasing vessel permeability (Thomas et al, 2005). The enhanced angiogenic activity could sustain growth of the primary tumour, potentiate dissemination and also support the establishment of micrometastases (Onesto et al, 2006). This is consistent with the strong association observed in different studies between VEGF-A expression and distant recurrence.…”
Section: Vascular Endothelial Growth Factor-a (Vegf-a)supporting
confidence: 79%
“…However, the status of VEGF-A remains unclear since other HNSCC retrospective studies have shown no correlation between VEGF-A expression and prognosis (Onesto et al, 2006;Thomas et al, 2005). These conflicting results may be due partly to the method of detection of VEGF-A expression (i.e.IHC), used in most of the previous reports, and which is a semiquantitative method.…”
mentioning
confidence: 44%
See 2 more Smart Citations
“…Using ELISA to quantify VEGF levels, one study showed that VEGF expression is associated with poorly differentiated head and neck cancers, higher rates of disease recurrence, metastatic disease, and shorter progression free survival. 98 Other studies have used laser capture microdissection followed by RT-PCR to compare VEGF mRNA levels in HNSCC with normal mucosa. A greater than seven-fold increase was found in the cancer samples.…”
Section: Response Prediction Of Anti-angiogenic Agentsmentioning
confidence: 99%